Analysis of The Financial Performance of PT Wijaya Karya (Persero) Tbk Based on Economic Valueadded Method on The Indonesia Stock Exchange - Kartiwa, Aa; Afrianti, Milla Ardhia; Dewi, Kisthi Hanila; Kurnia, Aura Diva; Wahyuni, Dini (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2025)
A significant contributor to the expansion of the national economy is the building industry. As a construction business, PT Wijaya Karya (Persero) Tbk must have good financial management. The EVA technique of financial performance analysis is required to determine if the business can generate economic added value and draw in investors despite the current economic difficulties. By using the EVA technique, this research seeks to ascertain PT Wijaya Karya (Persero) Tbk's financial performance over the 2019–2023 timeframe. Utilizing a qualitative approach and secondary data gathered from the company's yearly financial records, this research examines how PT Wijaya Karya (Persero) Tbk's financial success is measured using the EVA. NOPAT, IC, WACC, CC, and EVA are the analytical techniques used in this research. The 2019–2023 period saw changes, according to the findings of the Economic Value Added method study. In 2019, the firm created an EVA value > 0, in 2020–2022, it produced an EVA value < 0, and in 2023, it produced an EVA value